Effect of Gondorukem (Arpus) Adhesive Composition on Organic Waste-Based Briquettes using Biodrying Technology - Ridwandi; Dewi, Rozanna; Zulnazri, Zulnazri; Sylvia, Novi; Riza, Medyan (Indonesian Journal of Chemical Analysis (IJCA), 2025)
Briquettes are an alternative to coal, wood, and fossil fuels. Briquettes can be made with simple, inexpensive materials. The adhesive is gondorukem (arpus), which is easy to find. Making briquettes involves preparing raw materials, mixing adhesives with organic waste, and testing the finished product. The adhesive variations used were 5, 10, 15, 20 and 25%. Briquettes made with 5% gondorukem (arpus) adhesive had the lowest ash content. Briquettes with 25% gondorukem (arpus) had the highest ash content at 8.31%. Adhesives affect ash content. Moisture content analysis obtained with a value of 9.49% to 10.30%, the value is stable. The volatile content is 3.41-4.66%, which meets the SNI 01-6235 2000 standard. Calorimetry, all samples except 5% adhesive meet SNI 01-6235 2000 with minimum 5000 Cal/g (20934 J/g). Briquettes had density values of 0.0034176-0.004359 g/cm³, affecting energy content and combustion. Bound carbon analysis showed that all samples met the standard value of SNI 4931-2010. The burning rate of organic waste-based briquettes with different adhesives is 27 to 39 minutes, with a weight of 3.108 to 4.753 g/min. Briquettes take 66-111 seconds to ignite. SEM analysis shows rod-shaped substances, indicating organic waste and adhesives. The fibers visible are from the organic waste.